Starzenie się społeczeństwa. Wymiar społeczny, gospodarczy i polityczny - Zamorska, Katarzyna; Makuch, Marta (Księgarnia Akademicka, 2018)
Old age and the aging process of societies is now the main feature of European demography. The number of people aged 60+ is expected to increase in the world in 2050 over three times, which means that the participation of seniors among the general population will be significantly higher. Old age and the aging of societies is not a peripheral problem, as evidenced by the recognition of it in the late 1990s by the European Union as an issue that is common to all Member States. Along with such civilization challenges as globalization and technological progress, old age has been identified as an important factor of changes in Europe. The authors of the book still do not perceive the title issue only in the context of a threat. The purpose of the book is to capture the complexity of the problem of old age by presenting various aspects of it. The book structure therefore includes some of the most important issues that were discussed in the next seven chapters. In each of them, the authors rely on sources and research works of gerontologists, representatives of medical circles, sociologists, social politicians, as well as, authors whose interests go beyond the topic set by the frames of the book. Chapter 1 is an introduction to the title issue. Chapter 2 is an analysis of the demographic processes and consequences that led to the current situation. The political context of old age and aging is the content of Chapter 3, and continued in Chapter 4. Chapter 5 deals with the activity of older people in the labour market. The concept of "silver economy" was also discussed. Chapter 6 is devoted to the organization of care for old people - old age is not always successful, it is often a difficult period marked by suffering and poverty. The last chapter deals with the discussion about citizenship of seniors and their rights, which are de facto human rights.
Keywords: ageing; aging of society; activity; senior policy; universities of the third century; silver economy; care services; intergenerational solidarity; the rights of older people